PROFIL PEDAGANG KAKI LIMA LANSIA DI KECAMATAN TAMPAN KOTA PEKANBARU - Miftahur Riska; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Development of the number of street vendors has increased from year to year. There are 565 street vendorsIn district of Tampan. In this time there are still many elderly aged 60 years and above who are still working to meet their needs and their families. ElderlyStreet vendors in Tampan traded food, drinks, fruits and cooked dishes. The research method is qualitative with six informant. Street vendors in Tampan not only young but there are also elderly aged 60 years old. Male Elderly Street vendors is more dominant than female. ElderlyStreet vendors generallygraduated from elementary school and comes from a poor family. This elderly sellers trade in the morning till night until 11 pm. The average elderly traders this is only working one job only (do not have a side job). They can get Income Rp 50,000, up to Rp. 200,000,per day. The majority of the elderly sellers trade remained in one place and there was one person selling the informant in the circumference. Of the total informants came from the same area i.e. Pariamancity, West Sumatra. ElderlyStreet vendors seeking capital by borrowing to brother, boss or buyerand the capital of her own. Income or capital and join the income benefit per day. So, the net income fromelderly street vendors is not manyonly able to fullfill their everyday needs, but often they look for additional from elsewhere for their needs.Keywords: Street Vendors, Elderly, Informal Sector